Pepper production and income of pepper farmers in Lampung Province - Sutarni Sutarni; Fitriani Fitriani (Politeknik Negeri Lampung, 2014)
Pepper production Lampung grow slower and lower caused by among others 25,34% of plants on unyield condition. It also impacts on pepper export performance. This research aims to analize the factors influencing the pepper production and income of the farmers. Production centre in North Lampung is represented by Abung Tinggi subdistrict as research location. It was conducted on May until August 2012. Thirty pepper farmers were purposively choosen as respondents. They are members in farmer institution group at Pulau Panggung and Sukamarga villages. Analysis was done through Cobb Douglas production function and multiple regression. The result of research performed shows that the pepper production is influenced by seed, fertilizer, laborÂ¸ and dummy variable of institution performance. In the other hand, farmersâ€™ income has also been influenced significantly by pepper production, member of labors family, and dummy variable of institution performance.Key words: production, income, farmers institution